Full Employment: A Distant Dream for Europe - Indermit Gill; Johannes Koettl; Truman Packard (Institute for the Study of Labor (IZA), 2013)
Today, Europe is a continent of low participation, low employment labor markets. Many observers would like to blame poor employment outcomes on the Euro or on austerity. But these are dangerous distractions from real problems that constitute imperatives for structural reform. There are differences across countries, but there is a European model of work: almost every European economy has more stringent employment protection and more generous social benefits than peers in North America, Oceania, and East Asia. This has led to low labor force participation and high unemployment, especially among young Europeans. Layered on top of these weak labor markets is the rapid onset of aging; if policies are not changed, Europe will lose about a million workers every year for the next five decades, especially in the 2030s. In short, Europe has to increase both the demand for and supply of labor. To do so, Europeans have to begin viewing competition as a necessary good, not an unnecessary evil. Restructuring unemployment and pension benefits will help to increase participation and reverse the decline of the workforce, but policies that promote competition for jobs and mobility of job-seekers are needed to increase the demand for labor. To get to full employment, Europe has to alter the employment protection laws that give too much power to those with jobs while marginalizing others to the fringes of the economy. Europeans will have to reduce and restructure the generous social benefits that simultaneously discourage young people from searching seriously for work and encourage older workers to quit work too early. Europeans will have to view mobility of workers as a prerequisite of European integration, not just a possible consequence of it. If all this is augmented by reforms to reduce public debt, encourage enterprise and innovation, and stabilize finance, Europe will have a vibrant economy, with high participation and full employment.
Keywords: I38; J08; J21; J24; J32; J42; 330; employment protection; segmented labor markets; European labor markets; social benefits; labor mobility